Barriers and enablers to guideline implementation strategies to improve obstetric care practice in low- and middle-income countries: a systematic review of qualitative evidence. (December 2016) - Stokes, Tim; Shaw, Elizabeth; Camosso-Stefinovic, Janette; Imamura, Mari; Kanguru, Lovney; Hussein, Julia
Abstract Background Maternal mortality remains a major international health problem in low- and middle-income countries (LMIC), and most could have been prevented by quality improvement interventions already demonstrated to be effective, such as clinical guideline implementation strategies. The aim of this systematic review was to synthesise qualitative evidence on guideline implementation strategies to improve obstetric care practice in LMIC in order to identify barriers and enablers to their successful implementation. Methods We searched MEDLINE and CINAHL databases for articles reporting research findings on barriers and enablers to guideline implementation strategies in obstetric care practice in LMIC. We conducted a "best fit" framework synthesis of the included studies. We used an organisational "stages of change" model as our a priori framework for the synthesis. Results Nine studies were included: all were based in Sub-Saharan Africa and in hospital health care facilities. The majority of studies (seven) evaluated one particular guideline implementation strategy: clinical audit and feedback (both criterion-based audit and maternal death reviews), and a minority (two) evaluated educational interventions. A range of barriers and enablers to successful guideline implementation was identified. A key finding of the framework synthesis was that "high" and "low" intrinsic health care professional motivation are overall enablers and barriers, respectively, of successful guideline implementation. We developed a modified "stages of change" model to take account of these findings. Conclusion We have identified a number of quality improvement processes that are amenable to change at limited or no additional cost, although some identified barriers may be difficult to address without increased resources. We note the pathways to implementation may be complex and require further research to develop our understanding of individual and organisational behaviours and motivation in LMIC settings. Trial registration PROSPEROCRD42015016062